1995
DOI: 10.1071/mf9950137
|View full text |Cite
|
Sign up to set email alerts
|

Time-trend analysis of PAH and PCB sediment fluxes in the northern Baltic proper using different dating methods

Abstract: A recent laminated sediment was collected in the northern Baltic Proper with a Kajak-type gravity corer. The sediment core was analysed for content of polycyclic aromatic hydrocarbons, (PAHs) and mono-, di- and non-ortho polychlorinated biphenyls (PCBs). To evaluate different dating methods and to make dating as accurate as possible, four sediment-dating methods were used: activity measurements of the radio nuclides 210Pb, 239/240Pu and 137Cs, and counts of the number of laminae in the core. According to the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The burrowing of the amphipods feeding on the top millimeters mixes the sediment surface, which becomes a blend of the last few years' sedimentation. Additionally, the PCB concentration in Baltic sediments decreases very slowly [26] and could be assumed to be constant during the time span covered in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The burrowing of the amphipods feeding on the top millimeters mixes the sediment surface, which becomes a blend of the last few years' sedimentation. Additionally, the PCB concentration in Baltic sediments decreases very slowly [26] and could be assumed to be constant during the time span covered in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Jonsson (2000) estimated the mean sedimentation rate (±standard deviation) in offshore areas of the Baltic Proper and the whole Baltic Sea area to be 3.2 (±2.4) and 5.4 (±5.1) mm year− 1 , respectively. The sedimentation rate in the Baltic Proper was also estimated by Axelman et al (1995) and Neumann et al (1997) to be in the range 0.8-2.9 mm year− 1 . Thus, considering geographical and temporal variations, the sedimentation rate was estimated to range from approximately 1 mm year− 1 to more than 1 cm year− 1 , indicating that the top 1-2 cm sediment zone examined in the present study was deposited within the preceding ca.…”
Section: Sediment Samplingmentioning
confidence: 99%
“…For instance, data on the relative abundance of individual PCB congeners in a lake sediment [ Sanders et al , 1992] and in a peat core [ Sanders et al , 1995] showed no trend of decreasing relative amounts of less chlorinated congeners (Figure 2). Similarly, the congeneric composition in Baltic Sea sediments was found to be relatively constant in sediment layers from the period 1920–1990 [ Axelman et al , 1995]. Oliver et al [1989] found in a number of locations that the more recent sediment layers of Lake Erie actually contained a higher proportion of lower‐chlorinated congeners.…”
Section: Assessment Of Environmental Consistency Of a Large Ho· Sinkmentioning
confidence: 99%